Sly as a fox and cross as a bear - Phillips, Kathleen C. (Watts, 1968)
When the lion overhears the villagers comparing themselves to the animals, he decides that the animals must set a better example. However, when the mouse is not quiet and the cat and the dog don't fight, the villagers have only each other with whom to compare themselves.